(untitled) - AGUSTINA, ELIASANTI (RETAIN : Journal of Research in English Language Teaching, 2014)
“DOLL STEPS” AS A BRAINSTORMING GAME TO IMPROVE THE SPEAKING SKILL IN PROCEDURE TEXT OF THE NINTH GRADERS OF SMPN I MOJOKERTO JOURNAL BY ELIASANTI AGUSTINA NIM. 102084007 ADVISOR Dra. THERESIA KUMALARINI, M.Pd. NIP. 19521014 197903 2 001 SURABAYA STATE UNIVERSITY FACULTY OF LANGUAGE AND ARTS ENGLISH EDUCATION DEPARTMENT ENGLISH STUDY PROGRAM 2014 “DOLL STEPS” AS A BRAINSTORMING GAME TO IMPROVE THE SPEAKING SKILL IN PROCEDURE TEXT OF THE NINTH GRADERS OF SMPN I MOJOKERTO Eliasanti Agustina English Study Program FBS Surabaya State University elia.englishedu2010@gmail.com Dra.Theresia Kumalarini, M.Pd. Lecturer of English Study Program FBS Surabaya State University kumala_rini52@yahoo.co.id ABSTRAK Pengajaran berbicara bahasa Inggris di banyak sekolah tidak memfasilitasi siswa untuk menjadi terampil. Akibatnya, keterampilan berbicara mereka masih kurang memuaskan. Dengan demikian, guru harus menggunakan cara yang tepat untuk mengajarkan keterampilan berbicara berdasarkan kebutuhan siswa. Di sini peneliti menyarankan guru untuk menerapkan permainan brainstorming bernama “DOLL STEPS” yang bertujuan untuk membantu siswa memiliki kesempatan yang sama untuk menjadi aktif dan kritis, membangun kebiasaan untuk berbicara menggunakann bahasa Inggris, berbagi dan mendapatkan pengetahuan, berbicara dengan fasih dan bebas , berkaitan dengan topik yang diberikan , siap dengan tugas inti dalam pelajaran berbicara, dan belajar untuk memperhatikan pembicara yang lain. Penelitian ini fokus pada berbicara teks prosedur. Penelitian kuantitatif eksperimental ini bertujuan untuk mengetahui bagaimana kemampuan berbicara siswa setelah penerapan "DOLL STEPS". Populasinya adalah siswa kelas Sembilan di SMPN 1 Mojokerto, sedangkan sampelnya adalah IX E sebagai kelompok eksperimen dan IX F sebagai kelompok kontrol. Untuk mendapatkan data, masing-masing kelompok diberi pre-test untuk menemukan kesetaraan kemampuan dan post-test untuk menemukan pencapaian yang berbeda. Peneliti menggunakan rumus t -test untuk menganalisa data. Hasil penelitian menunjukkan bahwa skor post-test dari kelompok eksperimen lebih tinggi daripada kelompok kontrol. Kesimpulannya, direkomendasikan kepada guru bahasa Inggris bahwa permainan “Doll Steps” dapat digunakan untuk mengajar keterampilan berbicara sehingga dapat mencapai target belajar bahasa Inggris . Keyword : “Doll Steps”, Keterampilan Berbicara , Teks Prosedur ABSTRACT The teachings of speaking in many schools do not facilitate students to be skillfull in speaking. Consequently, their oral skill is still unsatisfactory. Thus, the teacher has to use an appropriate way to teach speaking based on the students’ need. Here the researcher suggested the teacher to implement brainstorming game namely DOLL STEPS which aims to help students have the same chance to be active and critical, build a habit to speak English, share and get knowledge, speak in fluent and free way, be enganged with the topic given, be ready in the main speaking task, and learn to pay attention to other’s talk. This study focuses on speaking procedure text.This experimental quantitative research aims to know how the students’ speaking skill after the implementation of “DOLL STEPS” is. The population was the ninth graders of SMPN 1 Mojokerto, whose sample was IX E as the experimental group and IX F as the control group. To get the data, each group was given a pre-test to find their equality and post-test to find the different achievement. The researcher used t-test formula to analyze the data. The result of the study showed that the post-test scores of the experimental group were higher than those of the control group. Finally, it is recomended that English teachers use Doll Steps game in teaching speaking skill to meet the target of learning English. Keyword: Doll Steps, Speaking Skill, Procedure Texts INTRODUCTION English proficiency is a must in the era of communication and globalization. English is seriously learned by many people to have a good prospect in the communication and also to get more information of international world. It can be seen in Indonesia that English is learned by children from elementary school to students of higher education. Therefore, our government seriously provides the appropriate curriculum about this subject. English lesson in junior high school function as a tool of self-development of students in science, technology and art. After completing their studies, they are expected to grow and develop into individuals who are intelligent, skilled and personable also ready to take a role in national development. In line with the explanation above is Indonesian law number 20 year 2003 about National Education System Article 37 paragraph 1, one of them states that language study materials include a foreign language with consideration of foreign languages, especially English is an international language which is a very important utility in global society (2006 : 282). Hence, English language become the principle subject which determines student graduation. This is proven by the fact that English is the subjects that is always included in the national examination in accordance with the Regulation of the Minister of National Education Number 78 Year 2008 on National Examination for Secondary level in Article 6 states that the subjects tested in the examination include Indonesian, English, Mathematics, and Science. In the process of learning English, a teacher must be able to master the language pretty well. Moreover she must be able to master how to teach English properly and how to transfer knowledge and experience of the teacher to the learners. Thus, there has to be many efforts to do in order to create an interesting English learning that can motivate students to enhance learners’ capacity in learning English. That is why, it is recommended that the teaching of English, should bring English atmosphere in it. Being a good teacher, she should be able to bring it in teaching and learning process, because if the atmosphere can not be brought into the process, the students will not get a clear purpose, why they have to learn the lesson and what is the importance of learning it for their daily lives. According to Depdiknas (2006:307), the teaching of English consists of four language skills, namely listening, speaking, reading and writing and other three components, pronunciation, vocabulary and grammar. Each skill has different purposes to help students master English. The uppermost important language skill in learning English is a skill in oral communication or generally called speaking. As declared by Aliakbar & Jamalvadi, speaking is crucial since it is the vehicle of social solidarity, social rank, the business world and as a medium for learning language??. Learning objectives of speaking have been clearly stated in the English curriculum. The goal is students are able to communicate efficiently. "Learning speaking should improve the communication skills of learners to be able to express and learn to follow the appropriate social and cultural development" (Kayi, 2006: 1). Unfortunately the current condition shows that English Foreign Language (EFL) learners, in this term is Indonesian learners, are reluctant to speak English in the classroom. The problem is commonly found in EFL class. It is caused by some factors such as they do not have the confidence to do conversation in English, they are afraid of making mistakes and then laughed by their peers, they have limited vocabulary so that they know what to say in bahasa but not in English and many more. Sometimes the topic given is too high for them so they prefer to be silent. In addition, some students did not get a chance to speak in class because of the domination by particular learners. Consequently, students have fewer opportunities to learn from speaking than the more oral students. For sure it will affect to their ability and their score in speaking skill as well. Students who do not take charge in their learning are unable to take full advantage of learning opportunities. This is a problem that faces many Asian students who are generally more reserved than western students (Tsui , 1996). As teachers, we can try to overcome students’ problem by using suitable warm-up activities, in this case called brainstorming game. Basically the use of brainstorming game in teaching and learning activities is not a must considering the effectiveness and time required. However, occasionally it is necessary to use the game to support the implementation of learning English. Brainstorming game can facilitate and create a strong positive effect on the atmosphere and also relaxed for students in doing classroom learning activities, considering that English is still a scourge for most students. That warm-up activity also helps students to have an overview about the main speaking task. In addition, the nature of game is fun so it can increase students' motivation and able to overcome shyness. Consequently, they will be able to express their ideas freely because through playing the game they may not consider that they are learning. Implementation of learning strategy in SMPN 1 Mojokerto strongly support the achievement of the speaking purpose itself. Learning strategy requires students to be independent, critical, and active in expressing their opinion. However at the presentation time most of the students do not focus in listening to the speaker. Sometimes they are busy with their own tasks even do not appreciate the presenter. Moreover, frequently there are learners who like to cut the talks of presenter with things that are not discussed. This affects condition of other students and causes confussion in the classroom. Teachers will be exhausted to remind them repeatedly. Dealing with the issues above, a teacher needs appropriate strategy and media which can control the class order and boost students’ score in speaking English. There are some alternatives of speaking games that can be used in order to improve the students’ speaking ability. One of the games that can be used is the Doll Steps game. This game is actually taken from the Chain Story ideas that are commonly used in the teaching of narrative text and also Talking Stick, but the writer gives a little modification in the content of the media itself, so that produces a new media that is Doll Steps game. As a result students will pay attention to the presenter when she is speaking. This teaching strategy can be used in teaching any texts. Based on Competence Based Curriculum Issued (KTSP) 2006, there are five genres that are introduced to Junior High school students. Those are procedure, descriptive, recount, narrative and report text. Those kinds of texts are expected to be mastered by the students well. Among those genres, a procedure text is easily understood by the students as it is commonly found in their environment. The text can be found on the sachet of instant foods and beverages also on the box of electronic machine. Additionally, procedure text is a genre which has to be mastered by students, especially the ninth graders as it is already stated in Standar Isi and Standar Kompetensi. In procedure text, students are told the way how something is achieved by doing sequence steps. The text includes set of suggestion on how to do something, how to operate something and how to get to a certain place or direction. To apply Doll Steps for procedure text, the speaker gives direction or step. All students will be treated fairly. They will get same chance to speak, so it is expected by applying this game, students will be able to speak English effortlessly and without hesitant. Doll Steps will be very advantageous for teaching speaking procedure text of the ninth graders in SMPN 1 Mojokerto. This study will discus the activities during the learning process using Doll Steps. The implementation here will be different from the concept in general as it will be modified by the music so that students feel comfortable. Researcher found a previous study on the use of brainstorming carried out in Oral Communication classes at a Japanese senior high school which was observed by Culen (1998) entitled, “Brainstorming Before Speaking Task”. Brainstorming used was Information Gap. The evaluation of the study showed that an increase in speaking time and a more positive atmosphere are two benefits that brainstorming can bring to speaking class. Based on the background and the problems above, the research conducted to investigate how the students’ speaking skill after the implementation of Doll Steps is. METHOD Concerning with the research question in the previous chapter, the writer used experimental quantitative research design. According to Ary, (1985) in Denik lejar (2012) Experimental design refers to the conceptual framework where the experiment is conducted. There were two groups involved in this study, experimental group (class IX E ) and control group (class IX F), which were randomly assigned. The two groups were given a pre-test to examine whether they were in the equal level or not. Then the experimental group was given a treatment by using Doll Steps in their teaching and learning process for several times. On the contrary, the control group was taught conventionally. At the end, both of the groups were given a post-test to measure the effectiveness of Doll Steps for teaching speaking procedure texts to Junior High school. The population used in this research was the ninth graders of SMP Negeri I Mojokerto. The researcher chose two classes randomly as the samples. In this research, the researcher chooses probability sampling, especially cluster random sampling. After getting two classes, the researcher randomly assigned which one was the experimental group and which was the control group. The two chosen classes should be equal, to avoid any unexpected effect. In this study, the sample was class IX E as the experimental group, and class IX F as the control group. Each of them consists of 26 students. This study used test as the instrument. The tests consisted of pre-test and post-test. The items used in the tests were exactly the same. The pre-test and post-test were administered to know whether the model of learning is successful or not. From the two tests, the researcher got scores of speaking tests as the data. Before the tests were administered, a tryout was conducted to analyze the reliability of the test be used for pre-test and post-test also to know the appropriate test items for the students’ level. The try-out test was given to the students who were given neither pre-test nor post-test. The number of the test items was just 2 instructions in the form of oral test. The results showed that the test items had a high validity because all of the components of the test items were according to the standard competency (see table 1) and has been approved by the experts (lecture of UNESA and the English teacher of SMPN I Mojokerto). While to know the reliability, the researcher used interrater reliability method. It means, one test will be administered once, but it is scored by two people. If the result from those two people are same or almost the same, means the test are valid and can be used in collecting data. Therefore, for the results showed that the test items were in high validity and reliability. Table 1 Scale of Validity Test Item Standard Competency Validity How to send a picture through e-mail How to make a glass of iced lemon tea 4.2.1 Mengungkapkan makna dalam monolog pendek sederhana dengan menggunakan ragam bahasa lisan secara akurat, lancar, dan berterima untuk berinteraksi dalam konteks kehidupan sehari-hari dalam teks berbentuk procedure Valid Valid When the students came in front of the class and produced a monologue related to the lesson given, their performance was analyzed and scored based on some aspects. They are pronunciation, grammar, fluency, vocabulary, organization and comprehension. Each aspect has its own point and description. The measurement adopted from Oller (Language Tests at School, 1979, pp. 320-323). A quantitative data analysis was conducted in this study. The scores of students’ speaking tests were analyzed by using t-test formula because the result of the study was determined by the comparison of the post-test scores of the two groups. Moreover it is used to analyze the significant difference between the pre-test and post-test scores of the two groups. RESULT AND DISCUSSION Result The Implementation of Doll Steps in Teaching Speaking The research was done on December 9th up to 12th 2014. Furthermore, six meetings were needed to accomplish the research; try-out, pre-test, treatment 1, treatment 2, treatment 3, and post-test. It is held to find out the influence of using brainstorming game called “DOLL STEPS” to improve students’ speaking skill in Procedure text. It was investigated through comparing the mean scores of the pre-test and post-test between the experimental and control group. Below is the statistics table of scores of both groups in pretest and posttest. Table 2 Scores of Pre-test for Experimental and Control Group Based on the calculation of the scores, it was found that the mean of the pretest scores of the experimental group was 70.2 and the control group was 65.4. From the table above, it can be seen that the Tvalue of pretest of the Experimental and control group with the level of significance of .05 and 58 (60) degree of freedom was 1.3 and the Ttable was 2,009. If the T table was higher than the Tvalue . it means that there is no significant difference between Experimental and Control group. Oller’s speaking measurement considers that both of the groups belong to level 3. From those results, the researcher assumed that the members of the two groups had equal level of speaking ability before the treatments were given. Table 3 Scores of Post-test for Experimental and Control Group From the calculation, the Mean of Experimental group was 81.9 which belongs to level 3+ and the Mean of Control group was 66.8 which belongs to level 3. It was clearly seen that the scores of experimental group the Mean of experimental group was much higher than the Mean of control group. Moreover the level of experimental is one level above the control group. The scores also have a better improvement. It can be seen at the pretest, the mean of experimental group was 70.2 and belongs to level 3. It significantly increased at the post-test the mean of which 81.9 and belongs to level 3+. It is because the experimental group was given a treatment by using Doll Steps game. The game was able to help students to produce oral speaking text fluently. The significant difference of the post-test scores of experimental The T value of post-test scores of experimental and control groups with level significance .05 and 58 (60) degree of freedom was 8.9 and the T table was 2.009. From the table above, it can be seen that the result of T table was lower than the T value. Therefore, it shows that there was a significant difference between two groups. In other words, there was a significant improvement between those who were taught by using Doll Steps game. Discussion As stated in chapter II, Kattlen (2005:31) defines that speaking as an interactive process of constructing meaning involves producing, receiving and processing information. However, some teachers and pupils mean every sound which comes out of the mouth is called speaking activity. It is totally wrong since speaking is human daily activity in which human expresses the ideas through the oral words about his need, feelings and thought that he wants other people hear. It must use his oral words not the words from the texts, recorders or other people’s words. In the second chapter, it can be seen that speaking is a productive skill not a receptive skill, so here the speaker must produce meaningful words not copying or imitating. Therefore, it is necessary that students not only be able to pronounce words correctly but also produce oral words fluently in order to improve the speaking skill of the students, in this case is in a procedure text. Then, the researcher favored Doll Steps game as an alternative way to ease students creates a procedure text orally. The oral words should create spontaneously which means that the words must be original words from the learners. Moreover from the contrasting scores of the post-test between two groups, it can be stated that Doll Steps game can be an effective game for teaching speaking procedure texts. The test items consisted of two instructions. In this section, the researcher tried to analyze the findings of the research which was conducted in SMP Negeri I Mojokerto. The first analysis was about the pre-test scores of the experimental and control groups. The result of the pre-test showed that there was no significant difference of both groups. It means that the two groups have equal ability. The second analysis was the post-test scores of Experimental and control groups. Table 3 shows that the mean of post-test scores for Experimental group was higher than that of the control group. Furthermore, the calculation of the t-test showed that there was a significant difference of post-test scores of Experimental and Control group. It seems that the treatments given to experimental group was successful. Table 3 describes clearly that Doll Steps game is effective for teaching speaking procedure texts. It is supported by the result showed that the scores between experimental and control were significantly different. It caused by the treatments given to experimental groups affected the students’ speaking ability. The treatments were given three times. During the treatments, the researcher applied steps of Doll Steps game. At the first treatment, the researcher explained and modeled the steps of Doll Steps first. After the researcher explained the strategy and the material, the students were taught a procedure text by applying Doll Steps game. From several treatments, the researcher was sure that “Doll Steps” is effective as an alternative strategy for teaching speaking procedure texts for the ninth graders in SMP Negeri I Mojokerto. Applying Doll Steps allows the following benefits some of which are stated in the second chapter: It takes students to be a critical learner as they develop independence in practicing speaking. It allows students to practice freely. Here they may speak fearless as no one will cut or correct their says as long as it relates with topic given. All the students will be active speakers for they will get their turn to speak up. It engages students in speaking around the topic. It makes students learn to focus on what his friends’ saying because in this game they should listen to the step mentioned by their friends to continue the next step. It scaffolds speaking with a variety of texts in all curriculum areas. It helps students to have a habit in speaking English. It makes students easy to produce the procedure text orally in the main activity since this game gives them chance to take and share knowledge with each other. It creates good English athmosphere in class which brings fun and purpossive learning activity. 10. Learners learn to appreciate one another. In conclusion, the calculation of the post-test from experimental and control groups using t-test showed that there was significant difference between them. Moreover the scores of Experimental group increased rapidly. It is statistically proved that Doll Steps game is effective for ninth graders in SMP Negeri I Mojokerto to improve their ability to speak the Procedure texts. CONCLUSION AND SUGGESTION Conclusion According to the findings in this research, in the previous chapter, it can be concluded that the post-test scores of the experimental group, who were taught by using Doll Steps game are higher than those of the control group who was taught as usual. It was proven by comparing the mean of post-test between the experimental (81.9) which is considered as level 3+ and control group (66.8) with just in level 3 which is clearly stated by the statistical computation between those two groups. Moreover, it was found that the t value of the t-test (8.9) was higher than the t table (2.00). The result of speaking ability of the experimental group students showed that most of them are very good in spoken procedure with the 3+ level. Some of them got excellent scores with the level 4 even 4+. It means that most of them were able to speak the language with suffecient structural accuracy and vocabulary to participate effectively in most formal and informal conversation on practical, social, and professional topics. Whereas some of them who got 4 and 4+ level were able to use the language fluently and accurately at all levels normally pertinent to professional needs (Oller:1979). Therefore, the research question of this study has been answered well. From the findings above, it can be stated that the Null hypothesis, which stated that there is no significant difference in the speaking ability of procedure texts between the students who are taught by using Doll Steps game and those who are not is rejected. On the other hand, the alternative hypothesis which stated there is a significant difference in the speaking ability of procedure texts between the students who are taught by using Doll Steps game and those who are not is confirmed. It can be assumed that teaching speaking procedure texts to ninth graders by using Doll Steps game helps the students to create a procedure text orally in a fluent way and reach a higher achievement. If the teacher implements the Doll Steps game to teach speaking of procedure texts, the students will be able to produce oral procedure text not only easily but also well structured and fluently because from the Doll Steps game they will become confident and critical learners, use their previous knowledge for the speaking task, feel free and confident through the game. Through their friends’ sentences they will gain new knowledge such as new vocabulary and how to arrange a good procedure text, so that they can produce the oral text well. In conclusion, it can be said that Doll Steps game is one of the effective teaching speaking games that can be used to teach speaking production of procedure text in the classroom. Suggestion Based on the result of the study, the researcher recommends some advices which are essential. The suggestion may be beneficial for the English teachers and other researchers who conduct a study on speaking skill. For the English teacher Nowadays, when the teaching and learning process is no longer teacher centered but student centered, so the teachers should have some criterion namely: Creative teacher Creative means teachers can do variation in teaching process such as adapting and creating new technique, media, strategy or even game. Good facilitator It means that as a facilitator, teachers should be able to explore students’ ability, for instance courage them to solve their learning problem, produce much ideas, give same chance to each students, and give supportive feedback. Selective teacher Teacher should selective in choosing the media, technique, strategy and game used to teach. The things must be appropriate to the curriculum, need, proficiency, and age of the students so that the learning process can meet the target. From all the characteristics above, students will be excited in practicing English orally Linked to the 2006 curriculum, the objective is to make learners able to express the text orally to be used for communication purpose (BSNP, 2006:24). Accordingly, the teacher should use suitable way, one which is giving Doll Steps game. Doll Steps game can give benefits and be implemented as an appropriate game for the students to produce oral procedure texts.. For the other researchers Relating to the successful usage of brainstorming game called “DOLL STEPS” to boost speaking score of the ninth graders of SMPN 1 Mojokerto, other researchers who are interested in investigating speaking skill are recommended that they look further on other related aspects of this study. Furthermore, it is suggested to develop this study by exploring the use of this game for other kinds of genre, skills, and level of the students REFERENCES Ary, D., Jacobs, L. C., Sorensen, C. K., & Razavieh, A. (2010).Introduction to Research in Education (8th Ed). USA: Wadsworth engage Learning. Bartz, A. E. (2001). Basic Statistical Concept i Education and the Behavioral Science. Moorhead, Minesota: Concordia College. Brown, H. D. (2004). Language Assessment Principle ad Classroom Practices. San Francisco: Pearson Education. Cullen, B. (1998). Brainstorming Before Speaking Tasks. The Internet TESL Journal , VOL IV No. 7. Harmer, J. The Practice of English LAnguage TEaching (3rd edition ed.). Cambridge, UK: Longman. Hayriye, K. (2006). Teaching Speaking: Activities to Promote Speaking in a Second Language. The Internet TESL Journal , VOLl XII No. 11. Houston, H. (2006). A Brainstorming Activity for ESL/EFL Students. The Internet TESL Journal , Vol. XII, No. 12. Liu, T.-Y., & Chu, Y.-L. (2010). Using Ubiquitous Games in an English Listening and Speaking Course : Impact on LEarning Outcomes and Motivation. ELSEVIER , 1. Manshouri, F. (2008). Second Language Acquisition Research : Theory - Construction ad testinng. Newcastle, UK: Cambridge Scholars Publishing. Nunn, F., & Nunn, R. (2005). Guiding ESL Students Towards Independent Speech Making. The Internet TESL Journal , Vol. XI, No. 2. Oller, John. W. (1979). Laguage Tests at School : A Pragmatic Approach. Boston, Massachusetts, USA: Longman.